2018
DOI: 10.3233/cbm-170321
|View full text |Cite
|
Sign up to set email alerts
|

Low-level serum miR-24-2 is associated with the progression of colorectal cancer

Abstract: Serum miR-24-2 is a potential negative biomarker in the diagnosis of the progression of CRC patients and associated with biochemical indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…1d). As shown in Table 1, LINC00963 expression was related to TNM stage (P = 0.001), which diagnosis according to International Union Against Cancer (UICC) tumor TNM classification system [29], tumor differentiation status (P = 0.047), and lymph node metastasis (P = 0.007). The expression of LINC00963 in CRC cell lines was found to be significantly up-regulated in comparison with CCD-18Co (P < 0.001, Fig.…”
Section: Linc00963 Expression Was Significantly Up-regulated In Crc Cell Lines and Tissues And Was Related To The Poor Prognosis And Clinmentioning
confidence: 99%
“…1d). As shown in Table 1, LINC00963 expression was related to TNM stage (P = 0.001), which diagnosis according to International Union Against Cancer (UICC) tumor TNM classification system [29], tumor differentiation status (P = 0.047), and lymph node metastasis (P = 0.007). The expression of LINC00963 in CRC cell lines was found to be significantly up-regulated in comparison with CCD-18Co (P < 0.001, Fig.…”
Section: Linc00963 Expression Was Significantly Up-regulated In Crc Cell Lines and Tissues And Was Related To The Poor Prognosis And Clinmentioning
confidence: 99%
“…Until now, studies have reported that miR‐24‐2 is involved in the development of several tumours; for examples, miRNA‐24‐2 accelerates the development of tumours such as gastric cancer and breast cancer by enhancing the expression of oncogene c‐Myc . And miR‐24‐2 has gradually become an important marker for predicting cancer prognosis and tumour progression . Furthermore, miR‐24‐2 may act as an oncogene in clusters and promotes the metastasis of breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Another research suggests the protein arginine methyltransferase 7 (PRMT7) repressed by miR‐24‐2 controls pluripotent factors Oct4, Nanog, Klf4 and c‐Myc . Furthermore, miR24‐2 may act as tumour biomarker . Strikingly, the amplification of miR24‐2 was confirmed in gastric cancer (GC) .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can be observed in the circulation alone or combined with some proteins; also, they can be released directly into extracellular fluids and carried by microvesicles, mostly exosomes [ 70 , 71 ]. miR-129 is highly expressed in CRC plasma, while miR-24-2 levels are low in CRC serum, thus representing potential positive or negative biomarkers in the diagnosis of CRC patients [ 41 , 42 ]. A study showed that serum expression levels of five miRNAs (miR-31, miR-141, miR-224-3p, miR-576-5p and miR-4669) were significantly different between patients with colon cancer and healthy controls, suggesting their potential use as a miRNA panel for diagnosis of CRC [ 43 ].…”
Section: Clinical Utility Of Liquid Biopsies In Patients With Colomentioning
confidence: 99%